The relationship between ECG predictors of cardiac resynchronization therapy benefit - Halamek, Josef; Leinveber, Pavel; Viscor, Ivo; Smisek, Radovan; Plesinger, Filip; Vondra, Vlastimil; Lipoldova, Jolana; Matejkova, Magdalena; Jurak, Pavel (PloS one, 2019)
INTRODUCTION: Cardiac resynchronization therapy (CRT) is an effective treatment that reduces mortality and improves cardiac function in patients with left bundle branch block (LBBB). However, about 30% of patients passing the current criteria do not benefit or benefit only a little from CRT. Three predictors of benefit based on different ECG properties were compared: 1) "strict" left bundle branch block classification (SLBBB); 2) QRS area; 3) ventricular electrical delay (VED) which defines the septal-lateral conduction delay. These predictors have never been analyzed concurrently. We analyzed the relationship between them on a subset of 602 records from the MADIT-CRT trial. METHODS & RESULTS: SLBBB classification was performed by two experts; QRS area and VED were computed fully automatically. High-frequency QRS (HFQRS) maps were used to inspect conduction abnormalities. The correlation between SLBBB and other predictors was R = 0.613, 0.523 and 0.390 for VED, QRS area in Z lead, and QRS duration, respectively. Scatter plots were used to pick up disagreement between the predictors. The majority of SLBBB subjects- 295 of 330 (89%)-are supposed to respond positively to CRT according to the VED and QRS area, though 93 of 272 (34%) non-SLBBB should also benefit from CRT according to the VED and QRS area. CONCLUSION: SLBBB classification is limited by the proper setting of cut-off values. In addition, it is too "strict" and excludes patients that may benefit from CRT therapy. QRS area and VED are clearly defined parameters. They may be used to optimize biventricular stimulation. Detailed analysis of conduction irregularities with CRT optimization should be based on HFQRS maps.
Keywords: funkce levé komory srdeční; Bundle-Branch Block; lidé; výsledek terapie; Action Potentials; blokáda Tawarova raménka; elektrokardiografie; Humans; Ventricular Function, Left; Predictive Value of Tests; Cardiac Resynchronization Therapy; srdeční resynchronizační terapie; prostředky srdeční resynchronizační terapie; Electrocardiography; Electric Countershock; srdeční frekvence; Cardiac Resynchronization Therapy Devices; elektrická defibrilace; Treatment Outcome; akční potenciály; prediktivní hodnota testů; Heart Rate